1977
DOI: 10.1002/pssa.2210430230
|View full text |Cite
|
Sign up to set email alerts
|

Morphological stability study in binary alloys II. Stability of coherent concentration modulations

Abstract: The stability of a precipitated two phase structure is analysed with respect to changes in number and size of the precipitated domains, using the equilibrium interfacial concentration profile and width of part I of this paper, and keeping the precipitate volume fraction at a constant value. Thereby the total system energy may show an absolute minimum at a finite precipitate size, if the ratio η out of the interfacial self energy component and of the pair potential strength stays below a certain value in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The K-state hasamong other explanationsbeen associated with long-range order and short-range order. For the long-range ordered case, highly ordered particles in a partially ordered matrix ("disperse order" [9]) have been suggested, e.g. by [lOj, for anexplanationof the anomaly in the specific heat (see [2, 111 for a critical discussion) and by [8] who observed "small homogeneous coherent precipitates by matrix strain contrast" in a transmission-electron microscope, that were unable t o coarsen.…”
Section: Introductionmentioning
confidence: 99%
“…The K-state hasamong other explanationsbeen associated with long-range order and short-range order. For the long-range ordered case, highly ordered particles in a partially ordered matrix ("disperse order" [9]) have been suggested, e.g. by [lOj, for anexplanationof the anomaly in the specific heat (see [2, 111 for a critical discussion) and by [8] who observed "small homogeneous coherent precipitates by matrix strain contrast" in a transmission-electron microscope, that were unable t o coarsen.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the present computations, it was concluded that de-coarsening together with a decrease of the number of regions -Are with increasing Ta will take place. The decrease of Are with increasing Ta was also predicted for Cu-15AI by Aubauer's theory [48] for the stability of coherent concentration modulations.…”
Section: The Domain Concentrationmentioning
confidence: 56%
“…The consideration of concentration fluctuations in addition to the statistical concept of SRO can account for the onset of disperse-order formation. Such a consideration was used recently by Trattner and Pfeilner [53] and by Pfeiler et al [54] for explaining relaxation behaviour in alloys which do not follow a single exponential process [34,48,55].…”
Section: Equilibrium Attainmentmentioning
confidence: 96%
“…This is connected with a decrease of the interfacial energy density. All of this stands in contrast to the clustering case and is analysed in more detail in the second part [22]. Moreover, as a difference to plane interfaces an asymmetric concentration profile appears in case of a finite value of the precipitate size.…”
Section: Resultsmentioning
confidence: 97%
“…The constants yo and yl originate from pure-metal properties and are irrelevant for interface features, while y ( T ) , c,, and cB are derivable from the concerned phase diagram (as done in [22]). The density g(c) can be found by combining f ( c ) of (11) with the elastic energy, as it is performed in (3).…”
Section: Specification Of the Energy Density F And Of The Potential Szmentioning
confidence: 99%